2021
DOI: 10.1186/s12887-021-02878-8
|View full text |Cite
|
Sign up to set email alerts
|

Enteral feeding advancement and growth until 5 years in extremely preterm infants

Abstract: Background In-utero weight gain can be achieved in very preterm infants through rapid advancement of enteral feeds without increasing risk of necrotizing enterocolitis. There are concerns, however, that such rapid weight gain may lead to an increased childhood adiposity risk, although long-term data are sparse. Design This retrospective observational study included two well-characterized cohorts comprising 145 infants born at < 28 weeks or with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Toftlund et al (26) demonstrated that 56% of very preterm (<32 weeks) had a catch-up growth, defined as an increase by 1 SD, up to 2 years of age. However, as shown by Wiechers et al (27) in another cohort of children born <28 weeks or <1000 g the SDS for weight and body mass index still remained lower than the reference population at 5 years of age. This is consistent with the findings in this study.…”
Section: Feeding Problemsmentioning
confidence: 74%
“…Toftlund et al (26) demonstrated that 56% of very preterm (<32 weeks) had a catch-up growth, defined as an increase by 1 SD, up to 2 years of age. However, as shown by Wiechers et al (27) in another cohort of children born <28 weeks or <1000 g the SDS for weight and body mass index still remained lower than the reference population at 5 years of age. This is consistent with the findings in this study.…”
Section: Feeding Problemsmentioning
confidence: 74%